The Myth of Open Scholarship — On the Architecture of Access and the Quiet Return of Gatekeeping - Vale, Dorian (Museum of One, 2025)
Description The Myth of Open Scholarship — On the Architecture of Access and the Quiet Return of Gatekeeping advances the philosophy of Post-Interpretive Criticism (PIC), a contemporary framework in aesthetics and epistemology that redefines criticism as witnessing from within rather than interpretation. Written by Dorian Vale under the Museum of One—an independent, open-science-compliant research institute—this essay interrogates the paradox of modern “open access” systems and their hidden structures of exclusion. It situates open scholarship within a broader genealogy of institutional gatekeeping, showing how repositories, funding mechanisms, and metadata infrastructures reproduce the hierarchies they claim to dissolve. Through the ethical lens of witness aesthetics, Vale explores the relationship between legitimacy, moral proximity, and the politics of visibility in digital knowledge economies. The work stands as both philosophical critique and living evidence: a post-institutional research architecture that meets and exceeds OpenAIRE, DFG, and metadata interoperability standards. By constructing its own parallel scholarly infrastructure—complete with DOI, ISBN, research taxonomies, and open-data compliance—Post-Interpretive Criticism demonstrates that moral legitimacy can not only precede but also surpass institutional recognition. Now permanently archived across global repositories, this essay transforms critique into praxis and exclusion into permanence—marking a turning point in the evolution of contemporary aesthetic philosophy and independent scholarship. This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843), The Journal of Post-Interpretive Criticism (Q136530009) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen. A philosophical essay within the Post-Interpretive Movement, redefining art criticism as witnessing from within. It critiques the myth of “open access” and exposes how digital scholarship infrastructures reproduce hidden hierarchies. Through Post-Interpretive Criticism, it demonstrates a fully compliant, post-institutional research model that transforms exclusion into permanence and legitimacy into moral custodianship. Abstract The Myth of Open Scholarship — On the Architecture of Access and the Quiet Return of Gatekeeping is a critical-philosophical essay written within the doctrine of the Post-Interpretive Movement, a contemporary aesthetic philosophy that redefines criticism as an act of witnessing from within rather than interpretation. This work interrogates the paradox of “open access,” revealing how digital scholarship infrastructures—repositories, funding systems, and metadata regimes—reproduce the hierarchies they claim to dismantle. Through a synthesis of aesthetic ethics, institutional analysis, and archival philosophy, the essay examines how visibility without humility becomes performance, and how openness, when institutionalized, transforms into a subtle form of control. It situates Post-Interpretive Criticism (PIC) as both a theoretical and performative intervention: a self-sufficient research architecture that meets and exceeds open-science, metadata, and DFG compliance standards, demonstrating that moral legitimacy can precede institutional legitimacy. Now archived within the very scholarly infrastructures it critiques, this work functions simultaneously as analysis and artifact—a living enactment of its own thesis. It marks the first complete articulation of post-institutional custodianship: a framework for scholarship grounded in ethical presence, metadata transparency, and spiritual rigor. By transforming critique into compliance and exclusion into permanence, the essay reclaims the archive as a site of witness rather than authority.
The Myth of Open Scholarship , On the Architecture of Access and the Quiet Return of Gatekeeping
Post-Interpretive Criticism, Stillmark Theory, Message-Transfer Theory, MTT, Misplacement, Displacement, Aesthetic Displacement Theory, Theory of Misplacement, Absential Aesthetics, Witness Aesthetics, Adab for Art, Hauntmark Theory, Spiritual Criticism, Presence-Based Criticism, Custodianship of Art, Art as Ontology, Aesthetic Recursion Theory, Aesthetic Recursion, Viewer as Evidence Theory, Restraint in front of art, Moral proximity, Interpretive silence, Erasure as ethics, Temporal scarcity, Silence as method, Ontology of beauty, Aesthetic mercy, Language as violence, Art encounter ethics, Epistemology of witness, Philosophy of Art, Aesthetics, Art Theory, Contemporary Aesthetics, Comparative Aesthetics, Phenomenology and Art, Ethics in Art Criticism, Interpretation and Meaning, Criticism and Reception Theory, Epistemology of Art, Visual Culture Studies, Dorian Vale, Founder of Post-Interpretive Criticism, Post-Aesthetic Critic, Independent Philosopher of Art, Museum of One, Art Writer and Theorist, Aesthetic Philosopher, Custodian of Witness Aesthetics, Spiritual Aesthetics Movement, The Doctrine of Post-Interpretive Criticism, The Custodian’s Oath, The Canon of Witnesses, Art as Truth, Art as Presence, The Viewer as Evidence, Interpretation vs. Witnessing, Language as Custody, Erasure as Afterlife, Museum of One Manifesto, Alternative art criticism, New art criticism movement, Ethical art theory, Criticism beyond interpretation, Slow looking philosophy, Quiet philosophy of art, Radical art restraint, Witness over interpretation, Interpretive Restraint Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen. Q136329014 - Aesthetic Displacement Theory https://africarxiv.ubuntunet.net/handle/1/10438 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 https://africarxiv.ubuntunet.net/handle/1/10466 https://africarxiv.ubuntunet.net/handle/1/10467 https://africarxiv.ubuntunet.net/handle/1/10468 https://africarxiv.ubuntunet.net/handle/1/10469 https://africarxiv.ubuntunet.net/handle/1/10470 https://africarxiv.ubuntunet.net/handle/1/10471 https://africarxiv.ubuntunet.net/handle/1/10472 https://africarxiv.ubuntunet.net/handle/1/10473 https://africarxiv.ubuntunet.net/handle/1/10474 https://africarxiv.ubuntunet.net/handle/1/10475 https://africarxiv.ubuntunet.net/handle/1/10476 https://africarxiv.ubuntunet.net/handle/1/10477 https://africarxiv.ubuntunet.net/handle/1/10478 https://africarxiv.ubuntunet.net/handle/1/10479 https://africarxiv.ubuntunet.net/handle/1/10480 https://africarxiv.ubuntunet.net/handle/1/10481 https://africarxiv.ubuntunet.net/handle/1/10482 https://africarxiv.ubuntunet.net/handle/1/10483 https://africarxiv.ubuntunet.net/handle/1/10484 https://africarxiv.ubuntunet.net/handle/1/10485 https://africarxiv.ubuntunet.net/handle/1/10486 https://africarxiv.ubuntunet.net/handle/1/10487 https://africarxiv.ubuntunet.net/handle/1/10488 https://africarxiv.ubuntunet.net/handle/1/10489 https://africarxiv.ubuntunet.net/handle/1/10490 https://africarxiv.ubuntunet.net/handle/1/10491